Produksi Enzim Selulase Dari Bakteri Serratia marcescens KE-B6 Dengan Penambahan Sumber Karbon, Nitrogen dan Kalsium Pada Medium Produksi - Septiani, Arom; Wijanarka, W; Rukmi, MG Isworo (Bioma : Berkala Ilmiah Biologi, 2017)
The waste of cellulose in the agro-industry can be reduced by decomposing the cellulose polymer into glucose. This process was carried out by cellulase enzyme (EC 3.2.1.4) produced by cellulolytic bacteria. Bacteria required food as nutrition to survived their life, can be obtained through growth medium or enzyme production medium. Carbon, nitrogen and calcium belong to the essential nutrients contained in growth medium and enzyme production medium. The purpose of this study is to determine the effect of the addition of carbon, nitrogen and calcium source and the time of incubation on the production of cellulase enzyme from Seratia marcescens KE-B6 bacteria. This research used Completely Randomized Design (RAL) of Factorial Pattern with two factors. The first factor is the type of medium, the first medium is the standard medium (M1) and the second medium is enriched with carbon, nitrogen and calcium sources (M2), the second factor is the incubation time with 5 repetitions. The enzyme production is measured by the reducing sugar method. The data obtained were analyzed using Anova. The results showed that the addition of carbon, nitrogen, and calcium sources and incubation time did not affect the production of cellulase enzyme by Serratia marcescens KE-B6.Â Keywords: Cellulose, Cellulase enzyme, Serratia marcescens